The Insular Cortex Controls Food Preferences Independently of Taste Receptor Signaling - Oliveira-Maia, Albino J.; De Araujo, Ivan E.; Monteiro, Clara; Workman, Virginia; Galhardo, Vasco; Nicolelis, Miguel A. (Frontiers in Systems Neuroscience, 2012)
The insular cortex (IC) contains the primary sensory cortex for oral chemosensation including gustation, and its integrity is required for appropriate control of feeding behavior. However, it remains unknown whether the role of this brain area in food selection relies on the presence of peripheral taste input. Using multielectrode recordings, we found that the responses of populations of neurons in the IC of freely licking, sweet-blind Trpm5-/- mice are modulated by the rewarding postingestive effects of sucrose. FOS immunoreactivity analyses revealed that these responses are restricted to the dorsal insula. Furthermore, bilateral lesions in this area abolished taste-independent preferences for sucrose that can be conditioned in these Trpm5-/- animals while preserving their ability to detect sucrose. Overall, these findings demonstrate that even in the absence of peripheral taste input, IC regulates food choices based on postingestive signals.